2007
DOI: 10.2353/ajpath.2007.061185
|View full text |Cite
|
Sign up to set email alerts
|

Human Placental Hypoxia-Inducible Factor-1α Expression Correlates with Clinical Outcomes in Chronic Hypoxia in Vivo

Abstract: Placental hypoxia is causally implicated in fetal growth restriction and preeclampsia, with both occurring more frequently at high altitude (>2700 m; HA). The nuclear transcription factor hypoxia-inducible factor (HIF) may facilitate placental oxygen transport at HA by increasing erythropoiesis and placental angiogenesis. We therefore investigated HIF expression and its regulatory mechanisms in placentas from normal pregnancies at high (3100 m), moderate (1600 m), and sea level (75 m) altitudes. Moderate-altit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 65 publications
5
85
0
6
Order By: Relevance
“…The dominance of the brown color in the cells of placental tissue is particularly apparent fort rophoblast cells and also for endothelial cells from blood vessels in the placenta. This is consistent with previous studies showing that hypoxic conditions increased the expression of HIF-1α in the placenta in preeclampsia [9][10][11] . The decreased expression of eNOS in the placenta of mice with preeclampsia in this study was also proven by another research 8 .…”
Section: Discussionsupporting
confidence: 93%
“…The dominance of the brown color in the cells of placental tissue is particularly apparent fort rophoblast cells and also for endothelial cells from blood vessels in the placenta. This is consistent with previous studies showing that hypoxic conditions increased the expression of HIF-1α in the placenta in preeclampsia [9][10][11] . The decreased expression of eNOS in the placenta of mice with preeclampsia in this study was also proven by another research 8 .…”
Section: Discussionsupporting
confidence: 93%
“…The dominance of the brown color in the cells of placental tissue is particularly apparent fortrophoblast cells and also for endothelial cells from blood vessels in the placenta. This is consistent with previous studies showing that hypoxic conditions increased the expression of HIF-1α in the placenta in preeclampsia [9][10][11] . The decreased expression of eNOSin the placenta of mice with preeclampsia in this study was also proven by another research 8 .…”
Section: Discussionsupporting
confidence: 93%
“…31 Preeclampsia and fetal growth restriction are more common in high-altitude regions. Zamudio et al 32 indicated that pregnancy at high altitude (3100 m) and chronic hypoxia in vivo are associated with an increased expression of HIF-1␣, resembling that of preeclampsia. Therefore, up-regulation of miR-210 in preeclamptic placentas seems to be biologically relevant, yet functional targets of miR-210 in the placenta have not been identified.…”
mentioning
confidence: 99%